Reverse chemical ecology approach for the identification of an oviposition attractant for Culex quinquefasciatus. - Choo, Y.M.; Xu, P.; Hwang, J.K.; Zeng, F.; Tan, K.; Bhagavathy, G.; Chauhan, K.R.; Leal, W.S. (Proceedings of the National Academy of Sciences of the United States of America, 2018)
Pheromones and other semiochemicals play a crucial role in today's integrated pest and vector management strategies. These semiochemicals are typically discovered by bioassay-guided approaches. Here, we applied a reverse chemical ecology approach; that is, we used olfactory proteins to lead us to putative semiochemicals. Specifically, we used 7 of the top 10 odorant receptors (ORs) most expressed in the antennae of the southern house mosquito, Culex quinquefasciatus, and which are yet to be deorphanized. We expressed these receptors in the Xenopus oocyte recording system and challenged them with a panel of 230 odorants, including physiologically and behaviorally active compounds. Six of the ORs were silent either because they are not functional or a key odorant was missing. CquiOR36, which showed the highest transcript levels of all OR genes in female antennae, was also silent to all odorants in the tested panel, but yielded robust responses when it was accidentally challenged with an old sample of nonanal in ethanol. After confirming that fresh samples were inactive and through a careful investigation of all possible "contaminants" in the old nonanal samples, we identified the active ligand as acetaldehyde. That acetaldehyde is activating CquiOR36 was further confirmed by electroantennogram recordings from antennae of fruit flies engineered to carry CquiOR36. Antennae of female mosquitoes also responded to acetaldehyde. Cage oviposition and dual-choice assays demonstrated that acetaldehyde is an oviposition attractant in a wide range of concentrations and thus of potential practical applications.